2018
DOI: 10.1002/jcb.27178
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Upregulated microRNA‐485 suppresses apoptosis of renal tubular epithelial cells in mice with lupus nephritis via regulating the TGF‐β‐MAPK signaling pathway by inhibiting RhoA expression

Abstract: Lupus nephritis (LN) is a common and severe complication of systemic lupus erythematosus. Without intervention, LN may cause acute kidney injury and end-stage renal disease. This study aims to determine whether microRNA-485 (miR-485) affects renal tubular epithelial cells (RTECs) in LN mice via the TGF-β-MAPK signaling pathway by targeting RhoA. Renal tissue samples were initially extracted from 15 LN and 15 normal mice. RTECs were cultivated in vitro and grouped after transfection of different mimics, inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…HMCs with overexpression of miR-485 had reduced levels of proin ammatory factors (TNF-a, IL-1b, IL-6) [32]. As indicated by Tian et al, miR-485 overexpression decreased RhoA, which stimulated the proliferation of renal tubular epithelial cells (RTEC) but suppressed their apoptosis by modulating the RhoA-dependent TGF-β-MAPK pathway among lupus nephritis mice [31]. According to Wang et al, overexpressed miR-485 hinders cell proliferation and stimulates the airway smooth muscle cells (ASMCs) apoptosis via Smurf2-dependent TGF-β/Smads pathway among chronic asthma mice [44].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…HMCs with overexpression of miR-485 had reduced levels of proin ammatory factors (TNF-a, IL-1b, IL-6) [32]. As indicated by Tian et al, miR-485 overexpression decreased RhoA, which stimulated the proliferation of renal tubular epithelial cells (RTEC) but suppressed their apoptosis by modulating the RhoA-dependent TGF-β-MAPK pathway among lupus nephritis mice [31]. According to Wang et al, overexpressed miR-485 hinders cell proliferation and stimulates the airway smooth muscle cells (ASMCs) apoptosis via Smurf2-dependent TGF-β/Smads pathway among chronic asthma mice [44].…”
Section: Discussionmentioning
confidence: 88%
“…Roles of miR-485 have been identi ed in diabetic nephropathy progression and lupus nephritis mice, overexpression of miRNA-485 inhibits the production of proin ammatory cytokines [31,32]. MiR-485 exhibits down-regulation within CD4 + T cells in MS cases when compared with normal subjects [33].…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with this, we found that liver injury and liver fibrosis induced by repeated injection of TAA were prevented by Fasudil treatment (Figures 1 and 2 ). In addition, several studies have proved that RhoA/ROCK pathway activation promotes TGF-β1 secretion in several models[ 30 ]. As a RhoA/ROCK inhibitor, Fasudil inhibited the induction of TGF-β1 secretion in TAA-induced liver fibrosis, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…RhoA promoted the vitality of rat renal tubular epithelial cells (RTEC) in lupus nephritis (LN) mice and inhibited RTEC cell apoptosis. e key regulatory role of the RhoA/p38MAPK pathway in cell apoptosis has been determined [25].…”
Section: Discussionmentioning
confidence: 99%